The Role of Islamic Political Economy in Implementing The Globalization of The Asean Economic Community (AEC) - Muh Syaukin Muttaqin; Nurlailah; Susilowati (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
The ASEAN Economic Community (AEC) is the realization of a free market in Southeast Asia, which has been implemented gradually since the ASEAN Summit in Singapore in 1992. The establishment of the ASEAN Economic Community (AEC) aims to enhance economic stability in the ASEAN region and is expected to address economic challenges among ASEAN member states. This study employs a qualitative descriptive approach. In collecting data, the researcher seeks to identify factual information from the data gathered through the research process, which is then processed and analyzed. The analytical framework used in this study is an inductive approach, namely describing the concept of Islamic political economy in a specific manner based on theoretical and doctrinal foundations. The findings of this study indicate that Islamic political economy in the implementation of the ASEAN Economic Community in Indonesia aims to improve economic stability for both Muslim and non-Muslim communities within the ASEAN region, particularly in Indonesia, and is expected to address economic issues among ASEAN countries. The consequences of the AEC agreement include the free flow of goods among ASEAN countries, the impact of the free flow of services, the free flow of investment, the movement of skilled labor, and the free flow of capital. These developments may have both positive and negative impacts on Indonesia’s economy. Therefore, from the government’s perspective, strategies and measures have been undertaken to ensure that Indonesia is prepared and able to take advantage of the momentum created by the ASEAN Economic Community.